Sunflower meal with and without phytase supplementation in diets for silver catfish (Rhamdia quelen) juveniles - Weiler, Kátia A.; Pessini, Jhonis E.; Sanchez, Milena S. S.; Rodrigues, Mariana L.; Boscolo, Wilson R.; Pezzato, Luiz E.; Bittencourt, Fábio; Signor, Altevir (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: The cost of feed in fish farming can exceed 70% of the total costs. Thus, the feed industry have sought to formulate balanced diets including low-cost by-products. Objective: To evaluate sunflower meal as a partial substitute (0, 10, and 20%) for soybean meal, with or without phytase supplementation (1,500 FTU/kg) in isoproteic (27% crude protein (CP)) and isoenergetic diets (3,400 kcal/ED/kg of feed) for silver catfish (Rhamdia quelen) juveniles. Methods: A total of 360 fish (weight: 15.77 ± 0.56 g) were randomly distributed in 24 tanks in a completely randomized design following a factorial scheme (3x2) with 4 replicates. The fish were evaluated on the following variables after 90 days: productive performance, hematological variables, histology of intestinal tissue, bromatological composition of carcass, and composition of bone mineral matter. Results: 20% dietary inclusion of sunflower meal improved weight gain and protein efficiency. No difference was observed in the other treatments and no interactions were observed between the other factors. Conclusion: 20% sunflower meal can be included in the feed of silver catfish as a substitute for soybean meal. Phytase inclusion (1,500 FTU/kg) did not improve the nutritional value of the treatments.